GPCRs: The most promiscuous druggable receptor of the mankind - Khaled Alhosaini; Asim Azhar; Asma Alonazi; F Al-Zoghaibi (Saudi Pharmaceutical Journal)
All physiological events in living organisms originated as specific chemical/biochemical signals on the cell surface and transmitted into the cytoplasm. This signal is translated within milliseconds–hours to a specific and unique order required to maintain optimum performance and homeostasis of living organisms. Examples of daily biological functions include neuronal communication and neurotransmission in the process of learning and memory, secretion (hormones, sweat, and saliva), muscle contraction, cellular growth, differentiation and migration during wound healing, and immunity to fight infections. Among the different transducers for such life-dependent signals is the large family of G protein-coupled receptors (GPCRs). GPCRs constitute roughly 800 genes, corresponding to 2% of the human genome. While GPCRs control a plethora of pathophysiological disorders, only approximately one-third of GPCR families have been deorphanized and characterized. Recent drug data show that around 40% of the recommended drugs available in the market target mainly GPCRs. In this review, we presented how such system signals, either through G protein or via other players, independent of G protein, function within the biological system. We also discussed drugs in the market or clinical trials targeting mainly GPCRs in various diseases, including cancer.